(untitled) (The Pakistan Development Review, 2025)
“The water issue is critically related to climate change. People say that carbon is the currency of climate change. Water is the teeth.” Jim Yong Kim, Former President, World Bank 1. INTRODUCTION Water is the prime channel through which the impacts of climate change on the world’s ecosystems and livelihoods will be felt. Pakistan is already a water-stressed country, ranking 14 among the 17 ‘extremely high water risk’ countries. Climate change in the form of rising temperatures and extreme and less predictable weather patterns are projected to affect patterns of rainfall, snowmelt, river flows, groundwater and water quality in Pakistan. This can lead to an increase in both inter- and intra-country disputes over water sharing arrangements. Over the last two decades, Pakistan has been ranked among the top 10 most vulnerable countries of the world to climate change, with 10,000 fatalities due to climaterelated disasters and financial losses amounting to about 4 billion from 173 extreme weather events. The country is already facing climate-related threats to water resources as is evident from the change in monsoon patterns, receding glaciers, rising temperatures and recurrence of floods and droughts. The floods of 2010, 2011 and 2012 not only incurred human cost but also economic costs, resulting in economic growth on average at a rate of 2.9 percent instead of its potential rate of 6.5 percent. Prolonged droughts in Tharparkar in Sindh and Balochistan also caused loss to human life and livelihoods. Since mid of June 2022, Pakistan has been affected by worst floods caused by record monsoon rains and melting glaciers, costing the economy over US30 billion. Over 33 million people have been affected out of total population of 222 million, and around 1,400 people have been killed. One-third of the country is under water, with over 80 districts (out of 160 districts) in the country having been officially notified as ‘calamity hit’ – 31 in Balochistan, 23 in Sindh, 17 in KP, 06 in GB and 03 in Punjab. The paper aims to address the impact of climate change on water systems and people. 2. MAIN SOURCES OF WATER IN PAKISTAN With 2.8 percent of the global population, Pakistan accounts for 0.5 percent of global renewable water resources. In other words, with the fifth largest population in the world, Pakistan ranked 36 out of 184 countries in total renewable water resources compared to India’s rank at 8 th and Bangladesh’s at 12th in 2017. Pakistan is a ‘water scarce’ country with a per capita water availability of less than 1,000 cubic metres. In 1951, Pakistan had an abundance of water with 5,260 cubic metres per capita, however, the country became ‘water vulnerable’ in 1981 with less than 2,500 cubic metres of water availability per capita to ‘water stress’ in 1991 with less than 1,700 cubic metres of water (see figure 1). By 2025, Pakistan could face droughts as its per capita water availability is going to become ‘absolutely scarce’ with less than 500 cubic metres. Indus Basin accounts for 96 percent of total available freshwater resources in Pakistan and around 80 percent of the country’s freshwater originates from outside the country, making it extremely risky and vulnerable (see Table 1). Glacier melt, snow melt and rainfall runoff account for 10 percent, 55 percent and 35 percent of total water in the upper Indus respectively. Over 85 percent of total water in the Indus originates from the Upper Indus and is shared between Pakistan (53 percent of the total area of Indus), India (33.5 percent), China (6.7 percent) and Afghanistan (6.3 percent). Stream flow in the upper Indus basin is highly seasonal: approximately 80 percent of the volume of annual stream flow in the tributaries of the upper Indus basin occurs during the summer months of midJune to mid-September.